Análise da Efetividade do Estudo de Impacto Ambiental - EIA/RIMA na Carcinicultura: o Caso do Município de Aracati - CE - Gomes, Laécia Gretha Amorim (2009)
This dissertation proposes to examine the effectiveness of the Environmental Impact Assessment - EIA in the creation of captive shrimp from the perspective of the case study of an EIA prepared for the expansion of a shrimp project located on the Jaguaribe river in the city of Aracati. According to Bolea (1984) apud La Rovere (2001, p.11), the AIA can be defined as "studies to identify, predict and interpret, and prevent the consequences or environmental effects that certain actions, plans, programs or projects may cause to our health, to the human welfare and the environment." According to the author, these studies include alternatives to projects subject to licensing and further induce the engagement and participation of the society, representing not a tool of decision in itself but an instrument of knowledge at the service of the general population. Thus, this essay discusses, so qualitatively, the effectiveness of this study as a serious aid tool in decision making and management and environmental monitoring, and verify if it, nowadays, is not being used only as a mere bureaucratic obstacle for the licensing of projects. In order to achieve the objectives, were established in the methodology, some criteria for analysis, which are: analysis of alternative locations, area of direct and indirect influence, coherence and relevance of environmental diagnosis, assessment of environmental impacts, effectiveness of mitigating measures, environmental monitoring and participation of the communities involved. Besides these features, the Environmental Impact Report - RIMA was also considered as part of the Environmental Impact Assessment, which were discussed and analyzed, topic by topic, always comparing them with the due legislation, in particular, the CONAMA Resolution 001 / 86 and other specific resolutions, such as: CONAMA312/02, CONAMA 237/92, CONAMA 09/87. Moreover, these concepts were also discussed in the light of authors who have addressed this issue in the view of its effectiveness. For this, the theoretical tools that have guided this research were made by Sánchez (2006), Agra Son (1993), IBAMA (1995), which explained the initial concepts on Environmental Impact Assessment, and IBAMA (2005) in the Diagnosis of the Cearense shrimp, which presents data for the creation of captive shrimp in the city of Aracati and the theoretical aspects related to this topic. The expected results were not much different from what was originally thought and from the analyzed aspects, very little presented serious and committed information with the real function of this study. Thus, one can say, after reviewing all topics initially proposed, that the EIA regarding the shrimp project examined was not actively effective for not presenting itself as a consistent tool for public consultation, help in decision making, in management and in environmental monitoring.